Preparation of environmentally friendly acrylic pressure-sensitive adhesives by bulk photopolymerization and their performance. Issue 17 (10th March 2020) - Zhu, Menglu; Cao, Zhanshuo; Zhou, Haijun; Xie, Yijun; Li, Guohua; Wang, Nongyue; Liu, Yingchun; He, Lianqi; Qu, Xiongwei
Abstract : Polyacrylic pressure-sensitive adhesives based on butyl acrylate, 2-hydroxyethyl acrylate, and acrylic acid were prepared by a bulk polymerization process triggered by a radical photoinitiator under UV irradiation and UV-crosslinking. Abstract : Polyacrylic pressure-sensitive adhesives (PSAs) based on butyl acrylate (BA), 2-hydroxyethyl acrylate (HEA), and acrylic acid (AA) were prepared by a bulk polymerization process triggered by a radical photoinitiator under UV irradiation and UV-crosslinking. 1, 6-Hexanediol diacrylate (HDDA) with difunctional groups was introduced into the PSAs to modify semi-interpenetrating network structures. The effect of HDDA content on the pressure-sensitive performance was comprehensively tested. The viscosity of the prepolymer was measured by a rotational viscometer. Prepolymers obtained by a photoinduced process and UV crosslinking process were confirmed via Fourier transform infrared spectroscopy (FTIR). All double bonds participated in the copolymerization without any remaining monomers, which reflected the concept of green environmental protection. Gel content in the crosslinked portion was examined by Soxhlet extraction, whilst the soluble molecular weight of PSAs was characterized by gel permeation chromatography (GPC). The viscoelastic properties of polymer films were determined by dynamic mechanical analysis (DMA). The T g value and storage modulus ( G ′) of the PSAs were enhanced with the addition of HDDA. Moreover, three fundamental adhesive properties, i.e. loop tack force, peel force and shear strength of PSAs, were measured. The results showed that UV crosslinking technology achieved a good balance of the three forces with excellent pressure-sensitive properties.